Potential Vector Shelter for Malaria in South Central Timor Regency in Indonesia - Nisa Fauziah; Arie Galih Mohamad; Naufal Fakhri Nugraha; Lia Faridah; Jontari Hutagalung (Faculty of Medicine, Universitas Padjadjaran, 2020)
More than half of the areas in East Nusa Tenggara province, a province in the eastern part of Indonesia, are planned to be free from malaria by the end of 2030. However, one of the critical indicators for malaria elimination is still lacking, i.e. vectors’ environment and breeding place indicators. South Central Timor (SCT) District is one of the areas with the highest Annual Parasite Incidence (API) >2‰ with the majority of the population works as farmers. The purpose of this study was to capture the relationship between environmental factors and the prevalence of malaria. This study was a cross-sectional analytic retrospective study using data from a previous malaria study conducted in August 2013 to September 2014 in 5 sub-districts of SCT district. All respondents were selected using the systematic random sampling approach from the population of healthy people. Data were collected using a standard questionnaire and an observation environment form. Malaria was confirmed through microscopic and Polymerase Chain Reaction (PCR) examinations. Data were then analyzed using the bivariate and multivariate analysis with 95% CI and α:0.05. Of 357 data collected, 35% (125/357) were malaria positive based on PCR examination. Two variables (living nearby lagoon and nearby rice field) were significant (p-value<0.05) as vector shelters for Anopheles sp. Thus, these have to be included as inputs to formulate effective and efficient malaria elimination strategies and programs in 2030. Lokasi Potensial Perkembangbiakan Vektor Malaria di Kabupaten Timor Tengah Selatan, IndonesiaLebih dari setengah Provinsi Nusa Tenggara Timur di Indonesia timur akan menghadapi bebas malaria pada akhir tahun 2030. Namun, salah satu indicator penting untuk eliminasi malaria adalah pengukuran lingkungan dan tempat berkembang biak vector masih kurang. Kabupaten Timor Tengah Selatan adalah daerah dengan salah satu Insidensi Parasit Tahunan tertinggi di Indonesia dan mayoritas penduduknya bekerja sebagai petani. Tujuan dari penelitian ini adalah mencari hubungan antara faktor lingkungan dengan prevalensi malaria. Penelitian ini menggunakan studi potong lintang metode analitik, menggunakan data retrospektif dari penelitian sebelumnya yang dilakukan pada Agustus 2013 hingga September 2014 di 5 kecamatan di Kabupaten Timor Tengah Selatan pada. Responden dipilih secara acak sistematik dari orang sehat. Pengumpulan data dengan kuesioner standar dan formulir observasi lingkungan. Konfirmasi malaria dengan menggunakan metode mikroskopis dan PCR. Data dianalisis dengan bivariat dan multivariate dengan 95% CI dan α: 0,05. Total 357 data dikumpulkan, 35% (125/357) positif malaria dengan pemeriksaan PCR. Dua variabel (dekat dengan laguna dan dekat dengan sawah) signifikan (nilai-p<0,05) sebagai tempat perlindungan vector untuk Anopheles sp. Penelitian ini diharapkan dapat memberikan informasi rinci untuk merumuskan strategi dan program eliminasi malaria pada tahun 2030 yang efektif dan efisien.